The Implementation of Merdeka Curriculum in English Language Teaching in High School - Ni'mah, Farihatun; Wafa, Zaenul; Sulistiyaningsih, Eka Fanti (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
The curriculum in Indonesia has undergone several changes, one of curriculum changes is the 2013 curriculum to Merdeka curriculum. Merdeka curriculum is a new educational approach that aimed to give more freedom to students in choosing how to learn. The aimed of this research is to clarify the implementation of Merdeka Curriculum in teaching English at high school and to find the problems encountered by teachers in the implementation of Merdeka curriculum at high school. The method used in this research was a qualitative descriptive method. The data collection process used observation, interview, and documentation techniques. The subjects of this research were three English teachers who had taken part in the Merdeka Curriculum training. The findings of this research indicate that the implementation of Merdeka Curriculum has been implemented at high school with direction from the Ministry of Education and Culture. The teacher creates learning outcomes, the flow of learning objectives, and teaching modules. Teachers also transfer the Pancasila student profile in implementing Merdeka curriculum. The problems faced by teachers in implementing Merdeka Curriculum are that teachers do not understand how to implement Merdeka curriculum, then the curriculum changes rapidly, and teachers also experience obstacles in using digital technology. Keywords: Implementation, Merdeka Curriculum, English Language Teaching.